2019
DOI: 10.34209/equ.v22i1.903
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Media Exposure Tehradap Pengungkapan Corporate Social Responsibility Perusahaan Manufaktur Terdaftar di BEI

Abstract: Social and environmental responsibility becomes one of the components of corporate disclosure listed on Indonesia Stock Exchange (BEI). This study examines the factors that influence the disclosure policy of social and environmental responsibility to manufacturing companies on BEI by expanding disclosure items. Factors suspected to affect social and environmental responsibility disclosure policies are media exposure, firm size, profitability and leverage. The research sample is a manufacturing company that dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
0
0
17

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 2 publications
2
0
0
17
Order By: Relevance
“…Leverage affects positively and insignificantly the corporate social responsibility disclosure. This finding confirms the result of a previous study conducted by Sparta and Rheadanti (2019). The study found that the leverage variable has a positive but insignificant effect on the corporate social responsibility disclosure.…”
Section: Resultssupporting
confidence: 91%
“…Leverage affects positively and insignificantly the corporate social responsibility disclosure. This finding confirms the result of a previous study conducted by Sparta and Rheadanti (2019). The study found that the leverage variable has a positive but insignificant effect on the corporate social responsibility disclosure.…”
Section: Resultssupporting
confidence: 91%
“…Therefore, it is consistent with the results of the research conducted Henriques & Sadorsky (1996). Research conducted by (Kristi, 2013;Plorensia & Hardiningsih, 2015;Respati & Hadiprajitno, 2015;Reverte, 2009;Sparta & Rheadanti, 2019) shows that media disclosure has a positive effect on CSR disclosure. From the above statement, the third hypothesis is proposed as follows: H3: PMED has a positive effect on CSR disclosure Profitability (ROA) is a factor that makes management free and flexible to disclose social responsibility to shareholders, so that the higher the level of company profitability, the greater the disclosure of social responsibility.…”
Section: Introductionsupporting
confidence: 86%
“…Media Exposure juga dapat mempengaruhi luas pengungkapan CSR. Menurut Sparta & Rheadanti (2019) Media Exposure didefinisikan sebagai bentuk ungkapan tekait pencapaian yang diperoleh perusahaan melalui kegiatan CSR dengan perantara media yang dimiliki perusahaan. Bentuk komunikasi CSR melalui media secara tidak langsung membuat reputasi perusahaan di mata masyarakat menjadi meningkat.…”
Section: Pendahuluanunclassified